The Development of Research-Based Learning Model with Science, Environment, Technology, and Society Approaches to Improve Critical Thinking of Students - Usmeldi, U.; Amini, R.; Trisna, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
Learning physics in SMAN 1 Bukittinggi was conducted through theories and practicum that verified the theories. The preliminary survey on the implementation of physics learning showed that teachers had not yet applied research-based learning. There were still many students who had not yet mastered the learning of physics. Supporting facilities such as physics laboratory and the equipment had been available, but they are not yet optimally utilized. Research-based learning model is one of learning models that can improve critical thinking skill and students’ learning outcome. The research is aimed at developing research-based physics learning model with Science, Environment, Technology, and Society (SETS) approaches which was valid, practical, and effective to improve students’ critical thinking. This research used a 4D model from Thiagarajan. The instruments of the research were interview guidance, observation sheets, validation sheet of the learning model and the instructional materials, questionnaire response of teachers and students, critical thinking skill test, and assessment sheet of skills and attitudes. The result of the research showed that the developed learning model and the instructional materials belonged to the category of valid which was in accordance with the expert judgment. The learning model and the instructional materials belonged to the category of practical based on the result of the observation, and the response of teachers and students. The implementation of Research-based Physics Learning with SETS approach was effective in improving critical thinking skills and learning outcomes of the students.